(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Black Rice Flour and Flax Seed Flour are incorporated into “Muffins” to improve their nutritional value and sensory qualities. They are consequently a delicious and healthy option among consumers looking for more nutritious snacks. Commercially available “Muffins” are prepared from refined flour that is nutrionally inferior in the quality. The desired outcome of the present study was assessed the sensory attributes of value-added bakery product “Muffins” prepared by incorporation of Black Rice Flour and Flax Seed Flour, nutritional analysis and microbial load of value added “Muffins” done by AOAC method. The statistical analysis of value added “Muffins “by variance (ANOVA), (C.D) techniques, “t-test” and cost estimation. Standard recipe “Muffins” served as a control (T0) with three treatment combinations, were prepared by replacing Refined Flour with different ratio of Black Rice Flour and Flax Seed Flour which were referred as T1, 25:45:30gm T2, 30:50:20gm and T3 35:55:10 gm respectively. value added “Muffins” are distinguished by the crumbly, moist structure and improved organoleptic characteristics. They were analyzed on Nine Point Hedonic Scale score card for different Sensory Attributes. The result revealed that T2 (9) was found to be the most acceptable regards to its overall proportion followed by T1(7.2), T0 (6.9) and T3 (7.0) were liked moderately by the Sensory Panel Members respectively. Nutrient content was significantly increased in Best Treatment T2 as compared to control (T0) and Microbial load i.e., Total Plate Count, Yeast and Mould count and Coliform count was found safe to consume till 7 days. So, it was concluded from the result that the value addition of Black Rice Flour and Flax Seed Flour at different level, can improve the sensory attributes, nutrient content and microbial load of enriched “Muffins” Through this, the costs are decreased while remaining acceptable and reasonable in comparison to the marketplace price.